The apotheosis of Captain Cook : European mythmaking in the Pacific - Obeyesekere, Gananath (Princeton University Press : Bishop Museum Press, 1992)
"In January 1778 Captain James Cook "discovered" the Hawaiian islands and was hailed by the native peoples as their returning god Lono. On a return trip, after a futile attempt to discover the Northwest Passage, Cook was killed in what modern anthropologists and historians interpret as a ritual sacrifice of the fertility god. Questioning the circumstances surrounding Cook's so-called divinity - or apotheosis - and his death, Gananath Obeyesekere debunks one of the most enduring myths of imperialism, civilization, and conquest: the notion that the Western civilizer is a god to savages. Through a close reexamination of Cook's grueling final voyage, his increasingly erratic behavior, his strained relations with the Hawaiians, and the violent death he met at their hands, Obeyesekere rewrites an important segment of British and Hawaiian history in a way that challenges Eurocentric views of non-Western cultures." "The discrepancies between Cook the legend and the person come alive in a narrative based on shipboard journals and logs kept by the captain and his officers. In these accounts Obeyesekere sees Cook as both the self-conscious civilizer and as the person who, his mission gone awry, becomes a "savage" himself - during the last voyage it was Cook's destructive side that dominated. After examining various versions of the "Cook myth," the author argues that the Hawaiians did not apotheosize the captain but revered him as a chief on par with their own. The blurring of conventional distinctions between history, hagiography, and myth, Obeyesekere maintains, requires us to examine the presuppositions that go into the writing of history and anthropology."--Jacket.